Rozwój marketingu drugiego obiegu - Tarka, Piotr; Grzesiowski, Maciej (Development of the second samizdat marketing, 2006)
The purpose of this article is to explain aspects of primary and contemporary marketing activities. It has been assumed, that contemporary marketing’s idea and objectives are nowadays prevailing and still growing in today’s market situation and conditions concerning companies and their activities based on management. New marketing driving management seems to be the most important for small companies, which effectively use it to achieve their market objectives.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (4); 2006; nr 1114, s. 233-241